AN ANALYSIS OF EVOLUTIONARY CRYPTOCURRENCY MARKET_x000D_ DYNAMICS - DÖNMEZ, CEM ÇAĞRI (My University, 2020)
The focus of this research is to describe and discuss future blockchain technology in relation to different formsof digital cryptocurrencies by investigating distinct characteristics and common features of cryptocurrencies onthe market. This research explores significant relationships between the major cryptocurrencies on the complexcryptocurrency market ecosystem, particularly Bitcoin and the most prominent altcoins based on historicalmarket capitalization data for the last two years. In this work cross-correlations between differentcryptocurrencies are examined in terms of changes in the market capitalization value. For the comparativeanalysis minimum spanning tree (MST) and hierarchical structure tree (HST) methods are applied in the contextof economic behaviour of cryptocurrencies with regard to global cryptocurrency market trends.

Bu araştırmanın amacı, kripto para piyasadaki kripto para birimlerinin ortak özellikleriyle birlikte farklı_x000D_ özelliklerini araştırmak, gelecekteki blokzinciri teknolojisin birbirinden farklı kripto para birimleri üzerinde_x000D_ etkileşimini tartışmaktır. Bu araştırma, karmaşık bir yapıya sahip olan kripto para piyasası ekosistemindeki_x000D_ başlıca kripto para birimi olan Bitcoin ve son iki yıl içerisinde verilere dayanarak kripto para piyasında değer_x000D_ kazanan altcoin'ler arasındaki ilişkileri incelemektedir. Yapılan çalışmada, kripto para birimlerinin fiyat_x000D_ değişimleri arasında çapraz korelasyon olup olmadığı, kripto para piyasası ekososteminin kapitalizasyon_x000D_ değerindeki değişiklikler açısından araştırılmıştır. Araştırmada kullanılan veri setini karşılaştırmalı analize_x000D_ uygulayarak, kripto para birimlerinin ekonomiksel davranışları incelenmiş, bu bağlamda küresel kripto para_x000D_ birimlerinin piyasa eğilimlerini inceleyerek asgari Yayılma Süreci (Minimum spanning tree) ve Analitik_x000D_ Hiyerarşi Süreci (hierarchical structure tree) yöntemleri kullanılmıştır._x000D_
EVRIMSEL KRIPTO PARA PIYASASI DINAMIKLERI ANALIZI